2019
DOI: 10.21608/jappmu.2019.43004
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Characteristics of Small Ruminant Smallholders in Four District of Northern Egypt

Abstract: The study seeks to characterize socio-economic and farm characteristics of small ruminant smallholders in four districts of northern Egypt. Structured questionnaire was used for data collection from 60 small ruminants' farmers and analyzed with descriptive statistics. Findings show that the average age of respondents included in this study was about 46.6±13.6 years and across the four districts farmer age was not significantly different. The present results showed a high illiteracy rate (75%) among small rumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…In addition, Abd El-Ati et al (2019) reported that in New Valley governorate, 61.4% of breeders have medium ages between 42 and 60 years, while the percent was 55.7% in Assiut governorate. This result is similar to the findings reported by Metawi et al (2019), who found that the average age of respondents included in their study in Damietta governorate was about 46.6±13.6 years, and about 95% of them were married. On the other hand, Lawal-Adebowale (2011) found that the average age of a farmer in Spain is 50.5 years.…”
Section: The Snail Habitatssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, Abd El-Ati et al (2019) reported that in New Valley governorate, 61.4% of breeders have medium ages between 42 and 60 years, while the percent was 55.7% in Assiut governorate. This result is similar to the findings reported by Metawi et al (2019), who found that the average age of respondents included in their study in Damietta governorate was about 46.6±13.6 years, and about 95% of them were married. On the other hand, Lawal-Adebowale (2011) found that the average age of a farmer in Spain is 50.5 years.…”
Section: The Snail Habitatssupporting
confidence: 91%
“…The average Egyptian household size is 4.4 people, which is less than the current result, according to the CAPMAS data from 2011. According to Metawi (2011), the average family size in the north coastal zone's rain-fed and irrigated farming systems was 7.8 people and 5.7 people, respectively. In the former farmed regions of Sharkeia Governorate, 6.4 individuals made up the average family.…”
Section: The Snail Habitatsmentioning
confidence: 99%
“…Small ruminants play a crucial role in the lives and economies of rural populations in Egypt, providing meat, milk, wool, and hair [ 30 ]. In this study, 200 animals, consisting of 141 sheep and 59 goats, presenting with respiratory distress symptoms, underwent clinical and bacteriological examination.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the emphasis is that small ruminants hold a unique position in smallholder agriculture due to their shorter production cycles, faster growth rates, ease of management, low investment capital, low risk of loss, low feed requirements, and greater adaptability to harsh environmental climates than large ruminants [ 9 , 10 ]. Unfortunately, little is known about small ruminant livestock production in Egypt’s rural areas [ 11 ]. A scarcity of food and water distinguishes deserts.…”
Section: Introductionmentioning
confidence: 99%